DETERMINATION OF THE PARAMETERS OF A MAGNETIC SPECTROMETER MODEL BASED ON EXPERIMENTAL DATA - Dovbnya, A. N.; Udovenko, S. G.; Shamraev, A. A. (Radio Electronics, Computer Science, Control, 2024)
The specialized controller for control of magnet spectrometer is develop.The parameters of analyzing magnet model will be used for adaptive regulator design are calculated by active experiment data.